Pathophysiology of green teeth due to hyperbilirubinemia: a literature review - Amat, Nur Araziemah; Kusumawardani, Anisa; Ardini, Yunita Dewi; Hasan, Taufiq Hidayat (John Wiley & Sons, 2021)
Background: Green teeth due to hyperbilirubinemia is an uncommon condition that is rarely encountered in the soci- ety and is aesthetically challenging. This literature review aims to study the pathophysiology of green teeth due to hyperbilirubinemia. Methods: A comprehensive English-limited data have been collected from various sources including articles published from Scopus, NCBI, ScienceDirect and books in order to reach a relevant solution. The keywords used for the litera- ture search are “green teeth”, “bilirubin”, “hyperbilirubine- mia”, “jaundice” and “tooth discoloration”. The timeframe included the articles obtained was from 2000 to 2020. Results: Hyperbilirubinemia, or clinically manifest as jaun- dice, indicates raised systemic bilirubin level due to altera- tion in bilirubin catabolism. Its high saturation leads to the entrapment of bilirubin pigments in dental hard tissue thus exhibiting green teeth. As for the intensity of green colour, it is described as directly proportion with the duration and degree of jaundice whilst some author described it as depend- able on the development of enamel. Conclusions: Green teeth occurs due to the elevated biliru- bin saturation which leads to the integration of the pigments to dental tissue. But the varying intensity of green colour are multifactorial.